Understanding electricity and electronics - Buban, Peter; Schmitt, Marshall Langdon, 1919- (New York : McGraw-Hill, 1975)
A textbook of the theory and practical applications of electricity and electronics.
Includes index.
Keywords: Electrical engineering -- Juvenile literature; Electrical engineering; Electronics -- Juvenile literature; Electronics